2002
DOI: 10.1590/s0074-02762002000300014
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Residual Effect of Two Formulations of Lambdacyhalothrin Sprayed on Palm Leaves to Rhodnius prolixus

Abstract: The insecticidal activity and residual effect of two formulations of lambdacyhalothrin were evaluated withAmerican trypanosomiasis is a zoonosis of great importance in Latin American countries and is produced by the hemoflagellate parasite Trypanosoma cruzi. This protozoan lives and proliferates in the gut of blood-sucking Reduviidae insects and can be transmitted to humans, producing heart and intestinal lesions described as Chagas disease (Ferro et al. 1995). Transmission by insect vectors represents 80% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Similarly, Okoh et al (2013) and (2014) achieved above 44.29% reduction in malaria infection and other morbidity indicators such as fever, hospital attendance, health seeking movement and school absenteeism in children of Oruku, Enugu state, Nigeria, with lambdacyhalothrin treated curtains, mats and blankets. Curtis and Mnzava (2000) achieved 60% reduction in malaria incidence with both spraying and impregnated netting intervention with lambdacyhalothrin in Kenya and United Republic of Tanzania; Miguel and Mazariego (2002) reported 100% effectiveness up to 12months after lambdacyhalothrin was sprayed on palm leaves against Rhodnius prolixus in the state of Chiapas Mexico.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Okoh et al (2013) and (2014) achieved above 44.29% reduction in malaria infection and other morbidity indicators such as fever, hospital attendance, health seeking movement and school absenteeism in children of Oruku, Enugu state, Nigeria, with lambdacyhalothrin treated curtains, mats and blankets. Curtis and Mnzava (2000) achieved 60% reduction in malaria incidence with both spraying and impregnated netting intervention with lambdacyhalothrin in Kenya and United Republic of Tanzania; Miguel and Mazariego (2002) reported 100% effectiveness up to 12months after lambdacyhalothrin was sprayed on palm leaves against Rhodnius prolixus in the state of Chiapas Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Curtis and Mnzava (2000) reported that both spraying and impregnated netting intervention with lambdacyhalothrin reduced malaria vector and hence malaria incidence by about 60% in Kenya and United Republic of Tanzania. Miguel and Mazariego (2002) observed 100% effectiveness up to 12 months, after lambdacyhalothrin was sprayed on palm leaves against Rhodnius prolixus in the state of Chiapas, Mexico. Above 44.29% reduction in malaria infection and other morbidity indicators such as fever, hospital attendance, health seeking movement and school absenteeism was achieved in children of Oruku, Enugu State, Nigeria with lambdacyhalothrin-treated curtains, mats and blankets (Okoh et al 2013(Okoh et al , 2014.…”
Section: Pyrethroid Insecticides Have Been Widely Used Formentioning
confidence: 95%